Regulasi Artemisin melalui Jalur CYP11A1 dan LONP1 dalam Mengobati Polycystic Ovarii Syndrome (PCOS) - Related Insulin Resistance - Margolang, Muhammad Dary; Hidayah, Nurul; Hudawi, Fairuz Alifia Aksalansia; Faramarisa, Fara Nayo; Nurhuda, Yusa Amin (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the therapeutic potential of Artemisia annua L. derivatives, specifically artemisinin, in modulating disrupted endocrine and metabolic pathways in PCOS. This research method utilized a literature review, with data sources consisting of journal articles and books related to the research topic. The results indicate that the pharmacological properties of artemisinin can treat PCOS-related insulin resistance through its regulatory interaction with the CYP11A1 and LONP1 pathways. Artemisinin can also enhance CYP11A1 degradation by directly binding to the mitochondrial protease LONP1, reducing androgen synthesis and alleviating insulin resistance. By targeting steroidogenesis and mitochondrial function, artemisinin emerges as a promising multi-target alternative therapy for PCOS with fewer side effects. In conclusion, artemisinin shows good molecular and clinical potential for overcoming insulin resistance in PCOS patients.   Keywords: Artemisinin, CYP11A1, LONP1, PCOS, Insulin Resistance